Trypanosomatids Methods and Protocols - Michels, Paul; Ginger, Michael; Zilberstein, Dan (Methods in Molecular Biology, 2020)
This volume explores the latest methods used by researchers to study different trypanosomatid parasites. These methods cover numerous disciplines, from organismal biology to molecular mechanism. The chapters in this book cover topics such as high-throughput sequencing; next-generation analysis of trypanosomatid genome stability and instability; DNA repair in cell extracts; ribosome profiling; and the use of CRISPR/Cas9 technology for gene editing. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and practical, Trypanosomatids: Methods and Protocols is a valuable resource for any researcher working with trypanosomatids and trypanosomatid-borne diseases.